BCL2-Family Dysregulation in B-Cell Malignancies: From Gene Expression Regulation to a Targeted Therapy Biomarker - Tessoulin, Benoît; Papin, Antonin; Gomez-Bougie, Patricia; Bellanger, Celine; Amiot, Martine; Pellat-Deceunynck, Catherine; Chiron, David (Frontiers in Oncology, 2019)
BCL2-family proteins have a central role in the mitochondrial apoptosis machinery and their expression is known to be deregulated in many cancer types. Effort in the development of small molecules that selectively target anti-apoptotic members of this family i.e., Bcl-2, Bcl-xL, Mcl-1 recently opened novel therapeutic opportunities. Among these apoptosis-inducing agents, BH3-mimetics i.e., venetoclax led to promising preclinical and clinical activity in B cell malignancies. However, several mechanisms of intrinsic or acquired resistance have been described ex vivo therefore predictive markers of response as well as mechanism-based combinations have to be designed. In the present study, we analyzed the expression of the BCL2-family genes across 10 mature B cell malignancies through computational normalization of 21 publicly available Affimetrix datasets gathering 1219 patient samples. To better understand the deregulation of anti- and pro- apoptotic members of the BCL2-family in hematological disorders, we first compared gene expression profiles of malignant B cells to their relative normal control (naïve B cell to plasma cells, n= 37). We further assessed BCL2-family expression according to tissue localization i.e., peripheral blood, bone marrow and lymph node, molecular subgroups or disease status i.e., indolent to aggressive. Across all cancer types, we showed that anti-apoptotic genes are upregulated while pro-apoptotic genes are downregulated when compared to normal counterpart cells. Of interest, our analysis highlighted that, independently of the nature of malignant B cells, the pro-apoptotic BH3-only BCL2L11 and PMAIP1 are deeply repressed in tumor niches, suggesting a central role of the microenvironment in their regulation. In addition, we showed selective modulations across molecular subgroups and showed that the BCL2-family expression profile was related to tumor aggressiveness. Finally, by integrating recent data on venetoclax-monotherapy clinical activity with the expression of BCL2-family members involved in the venetoclax response, we determined that the ratio (BCL2+BCL2L11+BAX)/BCL2L1 was the strongest predictor of venetoclax response for mature B cell malignancies in vivo.